Workshop on Classroom Instruction for English Teachers in South Konawe Regency - Syukri, Suhartini; Zur, Sarjaniah; Atikah, Dewi; Hakim, La Ode Abdur Rauf Rahman (Jurnal Abdimas, 2024)
This program-based community service (PkM) aims to improve the quality of English language learning at the Junior High School (SMP) level in South Konawe Regency through training in the form of classroom instruction and communicative practice activities. The method used in this activity is Asset-Based Community Services (ABCD) which involves English teachers as research subjects and main actors in designing, implementing and evaluating learning changes and improving existing competencies. Classroom Instruction training focuses on introducing innovative language learning methods that are relevant to the needs of junior high school students. In this case, the use of English for Teaching as the teacher's language of instruction in the classroom plays a very important role. This activity involves implementing a collaborative approach between teachers and PkM implementers as well as resource persons to identify the most effective learning strategies in the specific school context. Meanwhile, Communicative Practice Activities are focused on developing learning activities that promote active verbal interaction in English and are student-centered. It is hoped that the results of this activity can provide practical and useful guidance for junior high school teachers in improving the effectiveness of English language teaching. In addition, through a participatory process, it is hoped that a sustainable collaborative culture will be created among teachers to continue to improve the quality of English learning. Continuous evaluation will be carried out to measure the positive impact of implemented learning changes.